Translation, ideology, and creativity - Tymoczko, Maria (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Early translation studies scholars explored the relationship between translation and literary creation, showing that translation serves innovative purposes in literary systems that are in crisis, or that are weak or relatively young. Translation also acts as an ‘alibi ’for the introduction of difference. These early explorations leave out the role of ideology in the creative aspects of translation, a role articulated in both discourse theory and postcolonial theory. As a form of linguistic interface, translation introduces discourse shifts, destabilizes received meanings, creates altern ate views of reality, establishes new representations, and makes possible new identities. All these changes can produce creative results in a literary system and a culture. These creative dimensions of translation are particularly apparent in post-colonial contexts, illustrated here by the nexus of language interface, translation, and literary creativity in Ireland from the end of the nineteenth century to the present.